¿EL MONEY ORDER EN LAS EMPRESAS PERUANAS? “El nuevo instrumento financiero que contribuiría con el cierre de las ventas a distancia de las MYPES en el Perú” - Schmidt Urdanivia, Johannes (2012)
MYPES in Peru are quite related to the country’s development since the majority of Peruvian people earn their income from these economic units. However, there are still a lot to do in order to develop these kinds of organizations because many of them are “subsistence business” and therefore they are not competitive. Furthermore, one of the main important factors to obtain the growth of these companies is to develop alternative means of payment that may increase the confidence between suppliers and consumers. This also could be aligned with a “distance sales strategy” that will help expanding the markets and sales volumes for this business sector.